The impact of video review in karate kumite during a Premier League competition - Carlsson, T.; Berglez, J.; Koivisto Persson, S.; Carlsson, M. (International Journal of Performance Analysis in Sport, 2020)
The aim of the study was to investigate whether a) the option to make video-review appeals influences the match outcome; b) the number of video reviews differs depending on the time period during a match; and the rejected-to-approved-appeal distribution differs depending on the c) time period during the match, d) match status, and e) match category in karate kumite. Video recordings from 555 matches in a Premier League competition were analysed. Point(s) awarded after the video review(s) changed the match outcome for a total of 47 matches, which corresponded to 13.1% of the matches with video review(s). The number of appealed video reviews increased for each 30-s time period in the 3-min matches (P < 0.001). The rejected-to-approved-appeal distribution differed depending on the time period during the match (P = 0.0025) but not depending on match status and match category (both P > 0.05). For karateka who had fewer points than the opponent, the rejected-to-approved-appeal distribution differed between time periods (P = 0.017). The option for coaches to make video-review appeals for techniques that were not awarded point(s) by the judges increased the chance for a fair match outcome in elite karate kumite.